Research on Internal Control of Medical Technology Enterprises Based on Risk Management - Tang, Guo (Education Insights, 2026)
This paper takes medical technology enterprises as the research object and examines internal control issues from the perspective of risk management. Considering the distinctive characteristics of the medical technology industry, including rapid technological iteration, high research and development investment, extended innovation cycles, and strict compliance requirements, the study first elaborates on the necessity of strengthening internal control systems to support stable operation and long-term development. It then analyzes the main types of risks encountered by medical technology enterprises in the process of internal control implementation, focusing on market uncertainty, technological development risks, and operational compliance pressures. On this basis, the paper further proposes the construction path of a risk-oriented internal control framework, emphasizing the integration of systematic risk identification, comprehensive risk assessment, and targeted control activity design. By combining theoretical analysis with practical business scenarios, this study aims to provide structured and operable references for medical technology enterprises to improve internal control effectiveness, enhance risk response capability, and promote sustainable and orderly development.